Simulation of negative voltage ripples at the output of charge pump system and the microcircuit output of bipolar LM27762 DC–DC converter - V. K. Bityukov; N. G. Mikhnevich; V. A. Petrov (Российский технологический журнал)
The operation of the LM27762 bipolar DC–DC converter chip was simulated using WEBENCH software developed by Texas Instruments. The main attention is paid to the influence of the load current on the negative voltage ripples at the output of the charge pumping system and the chip output. The results of the calculations are compared with the results of the experiments. It is shown that the model of operation of the microcircuit created by the manufacturer is approximate. When the microcircuit operates in burst mode, which is realized at relatively low load currents, the discrepancies in the number of discharge – charge cycles, voltage poles at the output of the pumping system, and in the time intervals between bursts are very significant. The model does not allow obtaining data on the ripples of the negative voltage at the chip output. Experiments have shown that the very limited data on output voltage ripples given in the microchip documentation is underestimated. They significantly depend on the input and output voltage and load currents. The discrepancy between the experimental results and the simulation results obtained using the model of the manufacturer LM27762 showed that the actual perfection test of the microcircuits should be based on three factors: experiment, simulation and joint analysis of the obtained results. The simulation results of the operation of the LM27762 circuit board of bipolar DC–DC converter using the WEBENCH Power Designer software developed by the Texas Instruments manufacturing company are presented. The calculations are made at the company's website. For the experimental studies the ready-for-use test board of LM27762EVM test module, provided by the manufacturer of the LM27762 circuit board, is used. The use of the test board, simulator, and software developed by the manufacturer of the circuit board ensures to have no problem while comparing the simulation and experimental results, which can be associated with the use of circuit components with differing characteristics, or with the board layout. The technical documentation for the circuit board does not have information about the characteristics of the keys and capacitors used in the circuit board. Unfortunately, a description of the developed model is not available either. The information mainly concerns the influence of load currents on negative voltage ripples at the charge pump system output and at circuit board output. The simulation has shown that already at a load current of 40 mA, the control system starts operating with a permanent charge pump frequency, while, according to the results of the experiments, the control system continues to work in the pulse train mode even at a higher current of 50 mA. The pulse train for such current consists of 15 charge transfer pulses, the interval between the trains is 3 μs, and the increase in negative voltage per pulse train is also about 75 mV. The comparison made of simulation results and the results of the experiment have shown that the model of operation of the LM27762 circuit board, created by the manufacturer, is approximate. It has been established that owing to a large number of assumptions in the developed circuit board model, when it operates in the pulse train mode, which is realized at relatively low load currents, the discrepancies are rather significant in the number of discharge–charge cycles, the pulsation amplitude at the charge pump system output, and the time intervals between the pulse trains. The simulation of operation of the circuit board does not give data on the negative voltage pulses at its output. The experiments have shown that the data provided in the documentation on the circuit board output voltage pulses, though quite limited, are underestimated. They largely depend on the input and output voltage and load currents. In general, the comparison of the results of simulation of the operation of the charge pump system of the LM27762 circuit board, when it operates in the pulse train mode, and the corresponding experimental results shows that the coincidence of the calculation results and those of the experiment in terms of quality can be considered satisfactory. The discrepancy between the experimental and simulation results, obtained using the manufacturer’s LM27762 model has proved that the true testing of the quality of circuit boards requires three factors to be taken into consideration: experiment, simulation and joint analysis of the obtained results.